Organocatalytic Chemoselective Primary Alcohol Oxidation and Subsequent Cleavage of Lignin Model Compounds and Lignin. Issue 13 (14th June 2017) - Dabral, Saumya; Hernández, José G.; Kamer, Paul C. J.; Bolm, Carsten
Abstract: A one‐pot two‐step degradation of lignin β‐O‐4 model compounds initiated by preferred oxidation of the primary over the secondary hydroxyl groups with a TEMPO/DAIB system has been developed [TEMPO=2, 2, 6, 6‐tetramethylpiperidine‐ N ‐oxyl, DAIB=(diacetoxy)iodobenzene]. The oxidised products are then cleaved by proline‐catalysed retro‐aldol reactions. This degradation methodology produces simple aromatics in good yields from lignin model compounds at room temperature with an extension to organosolv beech‐wood lignin (L1 ) resulting in known cleavage products. Abstract : Follow your primary intuition ! An unprecedented route for the degradation of lignin model compounds and lignin is developed through catalytic oxidation of the primary hydroxyl groups in β‐O‐4 lignin units by a TEMPO/DAIB system [TEMPO=2, 2, 6, 6‐tetramethylpiperidine‐ N ‐oxyl, DAIB=(diacetoxy)iodobenzene]. This unique pathway widens the scope of the existing strategies in the area of lignin depolymerization.